2014
DOI: 10.1088/1367-2630/16/10/103040
|View full text |Cite
|
Sign up to set email alerts
|

Quantum and semiclassical phase-space dynamics of a wave packet in strong fields using initial-value representations

Abstract: We assess the suitability of quantum and semiclassical initial-value representations (IVRs), exemplified by the coupled coherent states (CCS) method and the Herman-Kluk (HK) propagator, respectively, for modeling the dynamics of an electronic wave packet in a strong laser field, if this wave packet is initially bound. Using Wigner quasiprobability distributions and ensembles of classical trajectories, we identify signatures of over-the-barrier and tunnel ionization in phase space for static and time-dependent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(73 citation statements)
references
References 70 publications
5
68
0
Order By: Relevance
“…The initial spread of the electronic wave packet has been shown to be necessary for a good quantitative agreement with the TDSE in the context of high-order harmonic generation (HHG) [53][54][55][56]. This initial spread seems to be very important for strong-field ionization as well, as recent phase-space studies revealed that orbit-based methods that incorporate this spread exhibit a nearly quantitative agreement with the TDSE, even if tunnel ionization is not properly accounted for [57]. In addition, in the very low-energy region of the spectra, the CQSFA simulation exhibits a marked discrepancy with respect to the TDSE result.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial spread of the electronic wave packet has been shown to be necessary for a good quantitative agreement with the TDSE in the context of high-order harmonic generation (HHG) [53][54][55][56]. This initial spread seems to be very important for strong-field ionization as well, as recent phase-space studies revealed that orbit-based methods that incorporate this spread exhibit a nearly quantitative agreement with the TDSE, even if tunnel ionization is not properly accounted for [57]. In addition, in the very low-energy region of the spectra, the CQSFA simulation exhibits a marked discrepancy with respect to the TDSE result.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the initial momentum and position spread that exists for the TDSE, but is absent for the CQSFA. In fact, recent studies on HHG [53][54][55][56] and strong-field ionization [57] indicate that this spread is necessary for a quantitative agreement with the TDSE.…”
Section: Discussionmentioning
confidence: 99%
“…Wigner functions have been widely employed in quantum optics and quantum information, but are underused in strong-field and attosecond physics. There are however studies of ionisation [18,40,43,44], rescattering [45,46] and entanglement [47] in this context. In strong-field ionisation, seminal studies [43] for a zero-range potential in a static field identified a tail that could be associated with a classical tunnelling trajectory far from the core region, and with tunnel ionisation close to the core.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, this reordering results in changes to the effective potential, giving a shallower potential than the form in coordinate representation such as that used in [42]. The kinetic energy term of the Hamiltonian is obtained through operator reordering and the potential terms through integration with equation (1).…”
Section: Modelmentioning
confidence: 99%
“…A similar version of the CCS method to that reported here has been used previously in Ref. [42] for the study of quantum dynamics in phase space. In Section II we provide the necessary theory in order to understand our results including an overview of the CCS method and its governing equations (sections II A and II B), a description of the theoretical model used to show the efficacy of the CCS method for generating HHG spectra (section II C) and a description of the necessary modifications made to the CCS method in order to model this system (section II D).…”
Section: Introductionmentioning
confidence: 99%